KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA KELAS UNGGULAN - —, Atiqullah (STAIN PAMEKASAN, 2011)
This Research expresses about perception of pre-eminent class in fulfilling the target in improving degree and capacities of school with sample model of certain class in class level. Study productivity motivation, technological facility, educator profesionalitas, curriculum of lifeskills vocational and payload of spiritualitas development, recruitment passe the achievement value, potency test of academic and special test in field of MIPA and also English. While leadership vision is to entangle educator and teaching staff in process of decision making supported by behavior, experience and head education . Some leadership resistance influencing is psychological factor, lack of support factor and faktor of SDM low and also less wellbalanced society demand factor.